Direct air capture of CO2: from insights into the current and emerging approaches to future opportunities - Zeeshan, Muhammad; Kidder, Michelle K.; Pentzer, Emily; Getman, Rachel B.; Gurkan, Burcu (Frontiers in Sustainability, 2023)
The rapid development of direct air capture (DAC)-based technologies has become critical in order to remove CO2 from the atmosphere and limit global warming to a maximum of 1.5°C. In this perspective, we provide a mini review of the current research on the emerging liquid- and solid-based sorbent materials to capture CO2, summarize the existing challenges of DAC-based technologies, and suggest future research directions to accelerate the development of DAC systems. In particular, the desired properties for a breakthrough sorbent that efficiently captures CO2 from the air and releases it are described.